If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8(5 + -4r) + -4(4r + 2) = -32 (5 * -8 + -4r * -8) + -4(4r + 2) = -32 (-40 + 32r) + -4(4r + 2) = -32 Reorder the terms: -40 + 32r + -4(2 + 4r) = -32 -40 + 32r + (2 * -4 + 4r * -4) = -32 -40 + 32r + (-8 + -16r) = -32 Reorder the terms: -40 + -8 + 32r + -16r = -32 Combine like terms: -40 + -8 = -48 -48 + 32r + -16r = -32 Combine like terms: 32r + -16r = 16r -48 + 16r = -32 Solving -48 + 16r = -32 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '48' to each side of the equation. -48 + 48 + 16r = -32 + 48 Combine like terms: -48 + 48 = 0 0 + 16r = -32 + 48 16r = -32 + 48 Combine like terms: -32 + 48 = 16 16r = 16 Divide each side by '16'. r = 1 Simplifying r = 1
| 75=16x^2+11 | | 4-4a-5a=-5 | | 2(x-3)+6=5 | | 5n-3n=9 | | 3(3-4)=4x+3 | | 6=5x-3(3x+6) | | 4x(x-8)+3(x-8)= | | 3x-6y=-5y+9 | | 74=-5(3k-6)+7(2k+6) | | 4+y^3=12x | | -2y=3(3)+1 | | x^2-11x+3k=0 | | 2x-10x+5=-5x+17 | | -2y=3(2)+1 | | 4(x-3)=2x-8 | | Z^6-8z^3+12=0 | | -2y=3(1)+1 | | 7x+14-12x=-x+12-x-19 | | -2y=3(0)+1 | | 7.1(c-11)+3.4c=(-7.1-c) | | 45000-5z=0 | | Log(3x+2)=5 | | [(x)(x)]-9x=-18 | | 4sc-7=5-2sc | | 2(9n-8)=10(n+8) | | x*.28+x=63 | | 0=-5t^2+13+6 | | [(x)(x)]+13x+42=0 | | 4(h+3)=3h | | 13(4-2x)-2(1+x)=8+5x | | [2x(x)]=4x | | 0=-5t^2+12t+6 |